Efficacy, safety and tolerability of Dihydroartemisinin-Piperaquine for treatment of uncomplicated falciparum malaria in pregnancy in Ghana. - Osarfo, Joseph (KNUST, 2025)
A thesis submitted to the department of global and international health, college of health sciences in partial fulfilment of the requirements for the Degree of Doctor of Philosophy in Public Health